Optimasi Kinerja Karyawan Sektor Konstruksi melalui Humble Leadership: Peran Mediasi OCB dan Employee Engagement - Nelci Selan; Unggul Kustiawan (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study aims to examine the influence of Leader Humility on Job Satisfaction, Employee Engagement, Organizational Citizenship Behavior (OCB), and Employee Performance in construction companies located in Tangerang. The research approach used is quantitative with the Structural Equation Modeling (SEM) method. Data were collected through online questionnaires using Google Forms, which were distributed to 250 respondents working in various construction companies in Tangerang. Data analysis was conducted using SmartPLS 4.0 software to test the relationship between variables and the validity of the model. The results show that Leader Humility has a significant positive influence on Job Satisfaction, Employee Engagement, and OCB, which in turn contribute to improving Employee Performance. However, the research findings also show that Job Satisfaction does not have a direct influence on Employee Performance, although it plays a role in shaping extra work behavior through OCB and Employee Engagement. These findings provide important insights for managers and organizational leaders, that the implementation of Humble Leadership can be an effective strategy to improve overall employee performance, through increased engagement, satisfaction, and proactive behavior within the organization.